Taxonomic notes on Dutch desmids VI (Streptophyta, Desmidiales): new species, newly described zygospores - van Westen, Marien; Coesel, Peter (Phytotaxa, 2014)
From the Netherlands, three desmid species are newly described to science: Actinotaenium spinosporum (with zygospores), Staurastrum brachiatoides (with zygospores) and Staurastrum quadriradiatum. In addition to that, zygospores of the rather rare species Staurastrum echinatum are described for the first time. Differences with similar-looking species are discussed.